The effect of macadamia oil intake on muscular inflammation and oxidative profile kinetics after exhaustive exercise. Issue 8 (21st February 2017) - Malvestiti, Rosane; Borges, Leandro da Silva; Weimann, Eleine; Junior, Edenilson Pinto da Silva; Levada‐Pires, Adriana Cristina; Dermargos, Alexandre; Lambertucci, Rafael Herling; Hatanaka, Elaine
Abstract : In this study, we evaluated the onset and resolution of inflammation in control and macadamia oil‐supplemented rats after a single session of exhaustive exercise. We also analysed the antioxidant enzymes catalase (CAT), glutathione peroxidase (GPx), superoxide dismutase (SOD), and thiobarbituric acid reactive substances (TBARS). Rats were supplemented for ten days with macadamia oil (25 mg/kg), which is rich in oleic and palmitoleic acids. On the 10th day, control and macadamia oil‐treated rats exercised to physical exhaustion. Plasma and muscular levels of pro‐inflammatory cytokines (tumour necrosis factor alpha [TNF‐α], interleukin‐1 beta [IL‐1β], IL‐6, cytokine‐induced neutrophil chemoattractant‐3 [CINC‐3], macrophage inflammatory protein‐3‐alpha [MIP‐3α]) and soluble L‐selectin were measured prior to, immediately after, and 2, 24, and 48 h after exercise. Our data revealed increases in the muscle concentrations of IL‐1β, L‐selectin, CINC‐3, and MIP‐3α in the group supplemented with macadamia oil compared with the concentrations in the control group. CAT also increased in the treated group, which is important because pro‐inflammatory cytokines precede growth factor production and might alter the muscle repair process. We concluded that inflammation resulting from exhaustive exercise was greater in animals that received macadamia oil than in control animals. Practical applications: There are potential benefits of using fatty acids in the treatment of injured muscles, and these substances have been used in several types of injured tissues. Macadamia oil intake alters muscle healing signaling by influencing the production of reactive oxygen species and inflammatory mediators. Therefore, it is reasonable to hypothesize that the intake of immunomodulatory supplements would be beneficial to the muscular recovery of an athlete following a strenuous exercise session. The muscle healing process has three phases: inflammation, new tissue formation and tissue remodeling, and these phases might be modulated by fatty acids. After an exhaustive exercise session, muscle inflammatory markers from macadamia oil‐supplemented rats are augmented in comparison to non‐supplemented animals. Our data revealed increases in the muscle concentrations of IL‐1β, L‐selectin, CINC‐3, and MIP‐3α in the group supplemented with macadamia oil compared with the concentrations in the control group. Abstract : The muscle healing process has three phases: inflammation, new tissue formation and tissue remodeling, and these phases might be modulated by fatty acids. After an exhaustive exercise session, muscle inflammatory markers from macadamia oil‐supplemented rats are augmented in comparison to non‐supplemented animals. Our data revealed increases in the muscle concentrations of IL‐1β, L‐selectin, CINC‐3, and MIP‐3α in the group supplemented with macadamia oil compared with the concentrations in the control group.